2016
DOI: 10.1155/2016/7570489
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Hydrogen Sulfide in the Ageing Kidney

Abstract: Aims. The study aimed to examine whether hydrogen sulfide (H2S) generation changed in the kidney of the ageing mouse and its relationship with impaired kidney function. Results. H2S levels in the plasma, urine, and kidney decreased significantly in ageing mice. The expression of two known H2S-producing enzymes in kidney, cystathionine γ-lyase (CSE) and cystathionine-β-synthase (CBS), decreased significantly during ageing. Chronic H2S donor (NaHS, 50 μmol/kg/day, 10 weeks) treatment could alleviate oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…We administered NaHS by the oral route for 5 months starting at the age of 18-19 months that reversed signaling changes and resulted in these salutary outcomes. Another group of investigators recently reported that intraperitoneal administration of NaHS to 16-month-old mice for 10 weeks stimulates well-known anti-oxidant pathways involving Nrf2 to ameliorate aging-related changes in the kidney (Hou et al 2016); however, that study did not explore the status of H 2 S or signaling mechanisms including IR activation. Our exploration of signaling identified inhibition of AMPK as a key feature of renal aging; administration of H 2 S stimulates AMPK activity that leads to mTORC1 inhibition and reduction in matrix protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We administered NaHS by the oral route for 5 months starting at the age of 18-19 months that reversed signaling changes and resulted in these salutary outcomes. Another group of investigators recently reported that intraperitoneal administration of NaHS to 16-month-old mice for 10 weeks stimulates well-known anti-oxidant pathways involving Nrf2 to ameliorate aging-related changes in the kidney (Hou et al 2016); however, that study did not explore the status of H 2 S or signaling mechanisms including IR activation. Our exploration of signaling identified inhibition of AMPK as a key feature of renal aging; administration of H 2 S stimulates AMPK activity that leads to mTORC1 inhibition and reduction in matrix protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we for the first demonstrated that H 2 S prevents Hcy-induced cellular senescence in HT22 cells. It has been confirmed that H 2 S prevents the process of senescence in the endothelium [42], kidney [45,46], vascular [47], heart [48] and brain [43] of mice. Furthermore, increasing the content of endogenous H 2 S by proper diet extends the life span of the aged mice [49,50].…”
Section: Discussionmentioning
confidence: 84%
“…Klotho –/– mice exhibit enhanced nitrotyrosine levels and reduced levels of antioxidative enzymes, including Mn-SOD in the kidney ( Kimura et al, 2018 ). Additionally, Hou et al (2016) demonstrated that the production of endogenous hydrogen sulfide (H 2 S) in the aging kidney is insufficient. Exogenous H 2 S can reduce renal oxidative stress in aging mice via a mechanism that involves enhanced nuclear translocation of Nrf2 and increased expression of antioxidative enzymes, including Mn-SOD ( Hou et al, 2016 ).…”
Section: Physiological Significance Of Manganese Superoxide Dismutasementioning
confidence: 99%